Emergency Appendectomy in UK: A Single Center Retrospective Cohort Study - Fahim, Muhammad; Abbasi, Sadia Ijaz; Belgaumkar, Ajay; Maheswaran, Ian (International Journal of Innovative Research in Medical Science, 2022)
Background: Emergency appendectomy is among the most common emergency surgical procedures performed worldwide. The current study looks at the local data on how the emergency appendectomies are performed in a district general hospital in England. Aim: The aim of the study was to assess the current state of surgical practice of emergency appendectomy in a single center in UK and to compare with current international practice of appendicectomy. Methods: A single center, retrospective study performed between May 2018 and October 2019. Data was collected with a protocol for18 months with 7-day follow up period for patients who underwent emergency appendectomy. Primary outcome measures were primary surgical approach and rate of negative appendectomy. Secondary outcome measures were rate of conversion, length of hospital stay and 7-day complication rates including surgical site infections, unplanned ED returns and readmission. Results: A total of 226 appendectomies were performed during study period of 6 months, out of which 212 met inclusion criteria. Mean age was 32 years with a range from 6 years to 92 years. Majority of the procedures (96.6%) were performed by laparoscopic approach with 3(1.4%) requiring conversion to open procedure during the study period. 47(22.2%) of patients did not show evidence of appendicitis on histological examination of resected specimen. More than 72% of patients were discharged home within 48 hours of hospital admission. Rate of SSI was less than 7.5%. Conclusion: Laparoscopic appendectomy is the preferred and safe surgical approach for emergency appendectomy; however, the rate of negative appendectomy is high when compared against international benchmark.